Faktor yang Berhubungan dengan Kecelakaan Lalu Lintas Pengemudi Sepeda Motor di Sumba Barat - Ngongo, Oktavianus Lede; Berek, Noorce C.; Talahatu, Anna Heny (Faculty of Public Health, Nusa Cendana University, 2019)
Transportation is a very important part of human life. In fact, the existence of a vehicle can improve all human activities in carrying out the occupied routine, but problems arise such as traffic jams and increased traffic accidents. The Minister of Transportation stated that 4 (four) people died every day due to traffic accidents, 72% occurred in Indonesia and 73.9% involved motorbikes. The incident was an indication that motorbikes were the main cause of traffic accidents and contributed the most victims. The traffic accident data of the East Nusa Tenggara POLDA in 2018 showed a trend of increasing traffic accidents in 2018. The level of population mobilization in the legal territory of the West Sumba POLRES is relatively high. Based on the annual report book of West Sumba POLRES in 2018 there have been traffic accidents with 126 cases. The study aims to determine the factors associated with motorcycle driver traffic accidents in the area of West Sumba POLRES in 2019. This type of research is a quantitative study using a cross-sectional study approach. This research was conducted at the West Sumba Police Resort with a sample of 53 people. Analysis of the data used the chi-square statistical test. The results of this study indicate that the factors associated with traffic accidents are age (p = 0.004), behavior (p = 0.008), and lamp conditions (p = 0.005).